Tissue engineering of articular cartilage: from bench to bed-side - Abdul Rahman, Rozlin; Ahmad Radzi, Muhammad Aa'zamuddin; Mohamad Syukri, Norhamiza; Md Nazir, Noorhidayah; Sha'ban, Munirah (Korean Tissue Engineering and Regenerative Medicine Society, 2014)
Degeneration or defect of articular cartilage is a major predicament and if it is left untreated, it may lead to progressive damage and disability affecting every one disregard of their age. Although nonsurgical management of articular cartilage injury has remained largely the same over many years, surgical treatment keeps on evolving. Restorative techniques, mainly the cell-based therapies and autologous or allograft transplants continue to expand, giving surgeons more options for biologic reconstruction of the articular surfaces. Hence the field of articular cartilage tissue engineering which seeks to repair, restore and improve injured or diseased articular cartilage functionality has aroused deep interest and holds great potential for improving articular cartilage therapy. However despite this great evolution, therapeutic uncertainty in the restoration of damaged cartilage using tissue engineering approaches still remains unclear for the surgeon treating patients to make evidence-based decisions. This paper will give a general idea to different level of audiences in understanding the concept of tissue engineering from bench to bed-side regarding recent developments in this exciting field.